2012
DOI: 10.1002/chem.201202367
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic versus Social Self‐Sorting of Oligophenyleneethynylene Derivatives: From Isodesmic Self‐Assembly to Cooperative Co‐Assembly

Abstract: Narcissistic versus social! The self-assembly of two structurally related oligophenyleneethynylene derivatives featuring polar or nonpolar peripheral chains is reported. Their remarkable narcissistic versus social self-sorting behaviour in aqueous media can be controlled by concentration and solvent changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 73 publications
1
34
0
4
Order By: Relevance
“…can shift the equilibrium towards the formation of independent or mixed aggregates. In a recent example, an increase in concentration was demonstrated to induce the transformation of two coexisting micellar associates made up of two different molecules into ribbon-like aggregates formed upon co-assembly of both molecules [34]. Although this behavior could be considered routine for self-assembled systems in isolation, the ability to influence particular binding events in multicomponent mixtures is far from being a trivial subject.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…can shift the equilibrium towards the formation of independent or mixed aggregates. In a recent example, an increase in concentration was demonstrated to induce the transformation of two coexisting micellar associates made up of two different molecules into ribbon-like aggregates formed upon co-assembly of both molecules [34]. Although this behavior could be considered routine for self-assembled systems in isolation, the ability to influence particular binding events in multicomponent mixtures is far from being a trivial subject.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the supramolecular properties of OPE derivatives are relatively well-understood, the ability of directing narcissistic or social self-sorting processes in these systems remains unexplored. Recently, we described the self-assembly of two structurally related OPE derivatives substituted with polar or nonpolar chains (Figure 6) and their narcissistic vs. social self-sorting behavior in aqueous media that can be tuned by concentration and solvent changes [34]. …”
Section: Self-sorting Processes In Extended Supramolecular Aggregamentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Furthermore, other weak interactions such as dipoledipole, 12 C-HŊŊŊX (X = Cl, O) interactions 10,11 and the hydrophobic effect, 13,14 when combined with aromatic interactions (also known as π-π stacking), can play an important role in the additional stabilization of supramolecular polymeric assemblies.…”
Section: -7mentioning
confidence: 99%
“…Oligo(phenylene ethynylene)s (OPEs) are highly extended, π-conjugated organic molecules, and are well-known for their ability to cooperatively self-assemble into a wide variety of supramolecular structures, driven by non-covalent interactions. [9][10][11]13,14 It has been also shown that OPEs are able to selforganize into microcrystalline lamellae 20 or into micrometric-size associates 21 as well as to amplify chirality 22 or to invert supramolecular handedness. 23 Furthermore, a recent study confirmed that the interchain π-interactions in OPEs have strong impact on the photophysical properties of the self-assembled materials.…”
Section: -7mentioning
confidence: 99%